FACTORS ASSOCIATED WITH MORTALITY IN PATIENTS HOSPITALIZED WITH COVID-19: PROSPECTIVE COHORT AT EDGARDO REBAGLIATI MARTINS NATIONAL HOSPITAL. LIMA, PERU - VENCES, MIGUEL ANGEL (2020)
Aim: To determine the associated factors with mortality of adult patients hospitalized with COVID-19. Methods: We conducted a prospective cohort study and included patients older than 18 years hospitalized with the diagnosis of SARS-CoV-2 infection. Those patients with a positive rapid serological test on admission, but no respiratory symptoms nor compatible images were excluded. We collected the data from clinical records. Results: A total of 813 adults were included, 544 (66.9%) with confirmed COVID-19. The mean age was 61.2 years (SD: 15.0) and 575 (70.5%) were male. The most frequent comorbidities were hypertension (34.1%) and obesity (25.9%). The most frequent symptoms on admission were dyspnea (82.2%) and cough (53.9%). A total of 114 (14.0%) patients who received mechanical ventilation, 38 (4.7%) were admitted to the Intensive Care Unit (ICU) and 377 (46.4%) died. The requirement for ventilatory support, greater lung involvement, comorbidities, and inflammatory markers were associated with mortality. It was found that for every 10 - year increase in age, the risk of dying increased by 32% (RR: 1.32 95% CI: 1.25 to 1.38). Those who required admission to the ICU and mechanical ventilation had 1.39 (95% CI: 1.13 to 1.69) and 1.97 (95% CI: 1.69 to 2.29) times the risk of dying compared to those who did not. Conclusion:  We found a high mortality rate in hospitalized patients associated with greater age, more elevated inflammatory markers, and more severe respiratory compromise.